The VIP trial: a randomised controlled trial of the clinical effectiveness of a Victim Improvement Package (VIP) for the reduction of continued symptoms of depression or anxiety in older victims of community crime in an English city - Victoria Vickerstaff; Vari M Drennan; Marta Buszewicz; Anthony Kessel; Gerard Leavey; Jonathan Cooke; Chris Brewin; Teresa Lee; Marc Serfaty; Jessica Satchell; Gloria Laycock (BMJ Open)
Background Older crime victims may be particularly vulnerable to psychological distress.Objectives To compare the clinical effectiveness of a Victim Improvement Package (VIP) to treatment as usual (TAU) for reducing continued crime-associated distress.Design A three-step parallel-group single-blind randomised controlled trial.Setting Police-reported victims of community crime aged 65 and over were recruited from 12 local authority areas in a major urban city in England, UK.Participants Selection criteria—inclusion: victims of community crime aged 65 years or more, with significant Generalised Anxiety Disorder (GAD-2) and Patient Health Questionnaire (PHQ-2) distress associated with the crime. Exclusion: type of crime, diagnosis, receipt of cognitive–behavioural therapy (CBT) in the last 6 months; an inability to participate in CBT; cognitive impairment. Participants were typical of our local authority population; 71% were female, 69% white, with the majority of crimes associated with burglary (35%) and theft (26%). 67% (88/131) of the randomised participants were included in the primary analysis.Interventions TAU was compared with TAU plus up to 10 sessions of a cognitively-behaviourally informed VIP, delivered by a mental health charity over 12 weeks.Primary and secondary outcome measures Timings are in relation to the crime; baseline (3 months), post-VIP intervention (6 months) and follow-up (9 months). The primary outcome was a composite of the Beck Anxiety and Beck Depression Inventories. The primary endpoint was 6 months.Results 24% (4255/17 611) of reported crime victims were screened, 35% (1505/4255) were distressed. Of 60% (877/1505) rescreened at 3 months, 49% (427/877) remained distressed. Out of our target of 226, 131 participants were randomised; 65 to VIP and 66 to TAU alone. 68% (89/131) completed the primary outcome (post-intervention). The VIP showed no overall benefit; mean VIP −0.41 (SD 0.89) vs mean TAU −0.19 (SD 1.11); standardised mean difference −0.039; 95% CI (−0.39, 0.31), although stratified analyses suggested an effect in burglary victims (n=27, standardised mean difference −0.61; 95% CI (−1.22, –0.002), p=0.049).Conclusions Community crime had long-lasting impacts. The police are ideally placed to screen for distress, present in 35% of victims, but only 58% of participants were recruited and the cognitive–behavioural therapy was not delivered competently. Further research on victim care and improving the delivery and quality of therapy is required.Trial registration number All procedures were approved by the University College London (UCL) Research Ethics Committee on 17 March 2016 (6960/001). International Standard Randomised Controlled Trial Number is ISRCTN16929670: https://doi.org/10.1186/ISRCTN16929670.